(untitled) (Journal of the College of Education for Women, 2018)
Praise be to Allah, Lord of the Worlds, teach the pen, taught the human what he didn’t know, Ihmad - Almighty - and thank him, and repent to him and ask forgiveness, which is the most forgiving, and bear witness that there is no god but Allah alone has no partner, gives and prevents, And I bear witness that Muhammad is a slave to Allah and his Messenger, who called for guidance and good speech and spoke, peace be upon him and his family and companions, and those who followed them until the Day of Judgment.